The Correlation between Anxiety and Blood Pressure Changes in Administering Computer-Based Competency Test of Ners Students - Apriza Apriza; Erlinawati Erlinawati; Mohammad Fauziddin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study aimed to determine the correlation between anxiety and changes in blood pressure in administering the Ners Students computer-based Competency test. The study used a sphygmomanometer to measure blood pressure and used a HARS tool for anxiety. The research design used is a quasi-experimental method with a non-equivalent pretest-posttest design. The analysis method uses quantitative analysis of chi-square correlations and dependent T-test statistical tests. The results showed no significant association between the anxiety facing computer-based competency tests and changes in students' blood pressure, as evidenced by a score of p = 0.216. There was a significant difference in the average score between anxiety before and after taking the computer-based test p= 0.042. There was no significant difference on average between blood pressure before and after taking the computer-based competency exam p=0.231. This research concluded that the anxiety experienced by students in taking competency exams does not affect changes in blood pressure.